The Role of Blockchain Technology on Zakat Institutions, A Way Forward: Literature Review - Mohamed, Mohamud Ahmed; Mohamed, Mahad Abdiwali; Mohamud, Omar Ahmed (International Journal of Membrane Science and Technology, 2023)
Financial Technology (Fintech) is rapidly transforming the financial industry, with advanced features enhancing speed, convenience, and accessibility. Islamic Financial Institutions (IFIs) and Islamic Social Institutions must adopt FinTech to remain resilient and develop innovative products and services. This qualitative study analyzes the function of Blockchain technology in Zakat institutions and the challenges faced in adopting it. It examines recent publications, focusing on Islamic Financial Technology, the financial sector, and non-financial sectors. However, this article search was limited to scholarly works. Using the library's database, Google Scholar, and the Emerald Insight database, the search is conducted for relevant, primarily peer-reviewed articles, using the appropriate filters and keywords. Therefore, the purpose of this article is to identify the role of Blockchain technology in Zakat institutions and therefore analyze the current challenge faced by Zakat institutions when adopting Blockchain technology. Blockchain technology, particularly in the financial sector, offers numerous opportunities for financial institutions. Smart contracts on blockchain technology offer more independent, transparent, and dependable transactions. Technology advancements impact industries, including Zakat, which is a critical concept in Islam. Zakat institutions can leverage blockchain technology to improve funding and distribution processes, overcoming challenges faced by traditional institutions. In Islamic Social Finance.